ANALISIS HUKUM FASILITAS BAGI INVESTOR DI KAWASAN EKONOMI KHUSUS BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL DAN UNDANG-UNDANG NOMOR 39 TAHUN 2009 TENTANG KAWASAN EKONOMI KHUSUS - Poltak UB. Panjaitan (Universitas Sumatera Utara, 2013)
ABSTRACT Special Economic Zone (SEZ) is a part of the development of an investment in which the investor is given facilities. Lightening form of investment facilities are not clearly defined in the SEZ thus require interpretation of the legislation related to the facility in question. This research is intended to address issues the consideration of the CIL (Capital Investment Law) and SEZ Law provide investment facilities specifically to investors, setting investment facilities to investors in SEZ and the role of central and local government in the framework of the provision of facilities to investors in SEZ.The CIL and SEZ Law provide investment facilities with economic considerations (use of natural resources for the purpose of welfare of the people), political considerations (political economic democracy) and legal considerations (legal certainty in the investment law reform in the future). Further facilities in the SEZ by setting CIL that facility for investors in particular land rights is not attractive facility because the facility of land rights have disallowed/revoked by the Constitutional Court. Other side of that facility in SEZ Law out of sync with the facilities specified in the related regulations.Last that the role of central and local government in the framework of the provision of facilities to investors in SEZs by the CIL and SEZ Law needed to ensure legal certainty on taxation in particular fiscal facilities. Keywords: Facilities, Investors, Special Economic Zones, Capital Investment.